2011
DOI: 10.1055/s-0031-1285094
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Methamphetamine Exposure on Childhood Growth Patterns from Birth to 3 Years of Age

Abstract: We examined the effects of prenatal methamphetamine (MA) exposure on growth parameters from birth to age 3 years. The 412 subjects included (n = 204 exposed) were enrolled at birth in the Infant Development, Environment and Lifestyle study, a longitudinal study assessing the effects of prenatal MA exposure on childhood outcomes. Individual models were used to examine the effects of prenatal MA exposure on weight, head circumference, height, and weight-for-length growth trajectories. After adjusting for covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Focusing on physical growth patterns, Zabaneh et al (2012) found children exposed prenatally to METH have a modest decrease in height during the first 3 years of life with no observed difference in weight, head circumference, or weight-for-length trajectories. Prenatal METH exposure also is associated with significantly reduced caudate nucleus volume and cortical thickness increases in perisylvian and orbital-frontal cortices Zabaneh et al, 2012). Diffusion tensor imaging (DTI) suggests lower diffusion and higher fractional anisotropy in METHexposed children at 3-4 years of age, indicating that fetal METH may alter white matter tracts .…”
Section: Psychostimulants Methamphetaminementioning
confidence: 96%
“…Focusing on physical growth patterns, Zabaneh et al (2012) found children exposed prenatally to METH have a modest decrease in height during the first 3 years of life with no observed difference in weight, head circumference, or weight-for-length trajectories. Prenatal METH exposure also is associated with significantly reduced caudate nucleus volume and cortical thickness increases in perisylvian and orbital-frontal cortices Zabaneh et al, 2012). Diffusion tensor imaging (DTI) suggests lower diffusion and higher fractional anisotropy in METHexposed children at 3-4 years of age, indicating that fetal METH may alter white matter tracts .…”
Section: Psychostimulants Methamphetaminementioning
confidence: 96%
“…Intrauterine exposure causes decreased growth parameters of exposed newborns [8] as well the decreased growth trajectory in the first 3 years of life [10]. Infants that have been exposed to concurrent cigarette smoke as well as methamphetamine in utero are more likely to have intrauterine growth restriction.…”
Section: Methamphetamine In Special Populations: the Pregnant Woman Amentioning
confidence: 99%
“…Infants that have been exposed to concurrent cigarette smoke as well as methamphetamine in utero are more likely to have intrauterine growth restriction. Other long-term consequences are neurobehavioral and include increased aggressive behavior, delayed acquisition of mathematics and language skills, and poorer visual recognition memory [10,11].…”
Section: Methamphetamine In Special Populations: the Pregnant Woman Amentioning
confidence: 99%
“…2 Unlike with other drugs of abuse, more women than men are first-time users and comprise one-half of those seeking treatment of MA use, raising concern for the impact of prenatal MA use on children. In 2009, 6.7% of those seeking treatment of MA abuse in the United States were pregnant women. 3 Research on the impact of prenatal MA exposure on child development is emerging from the only large, prospective longitudinal study of prenatal MA use, the Infant Development, Environment, and Lifestyle (IDEAL) study.…”
mentioning
confidence: 99%
“…3 Research on the impact of prenatal MA exposure on child development is emerging from the only large, prospective longitudinal study of prenatal MA use, the Infant Development, Environment, and Lifestyle (IDEAL) study. 4 Previous MA findings from IDEAL include increased small for gestational size at birth 5 and decreased length through 3 years, 6 poor quality of movement, low arousal, and increased stress signs in the newborn period 7 and poor grasping ability at 1 and 3 years of age. 8 The only comparable study conducted in Sweden showed increased drowsiness during the newborn period 9 and increased behavior problems in amphetamineexposed children.…”
mentioning
confidence: 99%